أحكام زواج مجهولي النّسب دراسة مقارنة بين الفقه الإسلامي والقانون الوضعي - حمادو, وفاء; بكاري, زينب (University of Eloued-جامعة الوادي, 2022)
"موضوع الدّراسة والذي تحت عنوان: ""أحكام زواج مجهولي النّسب دراسة مقارنة بين الفقه الإسلامي والقانون الوضعي""، وقد كانت إشكالية الموضوع الرئيسية هي: ""كيف عالج القانون الجزائري والشّريعة الإسلامية موضوع مجهولي النّسب؟""، حيث تندرج خطة عملنا هذا تحت مبحثين اثنين، فخصصنا المبحث الأول تحت عنوان: مفهوم مجهولي النّسب في الفقه الإسلامي والقانون الجزائري و كل ما يندرج ويتعلق به، والمبحث الثّاني تحت عنوان: بيان أحكام عقد الزّواج لمجهولي النّسب بين الشّريعة الإسلامية والقانون الجزائري. وفي الأخير وبعد جولة استطلاعية من خلال المصادر والمراجع الملمة بجوانب موضوع بحثنا توصلنا إلى بعض النّتائج أهمها: أنّ مجهول النّسب في الشّريعة الإسلامية والقانون الجزائري يعتبرون مجهولي النّسب أحد أفراد المجتمع عليهم واجبات ويتمتعون بحقوق، وعليه نوصي بالتّوعية الكافية التي تجعل النّاس يعون ويدركون حجم المأساة التي تخلفها هذه الجريمة وخطورتها على المجتمع وما يلحق صاحبها من الإثم والعقاب يوم القيامة. ""The subject of the study, which is under the title: “Provisions of Marriage of Unknown Lineage A Comparative Study between Islamic Jurisprudence and Positive Law”, whose main problem was “How did Algerian law and Islamic Sharia treat the issue of persons of unknown parentage?”, which we worked on in a two-investigative plan, we devoted the first topic to the concept of unknown parentage. Everything that is going on around them between Islamic jurisprudence and Algerian law, and the second topic is to clarify the provisions of the marriage contract for those of unknown parentage between Islamic Sharia and Algerian law. In this research, we have reached many results, the most important of which are: that the unknown parentage is Islamic Sharia and Algerian law consider the unknown parentage members of society who have duties and enjoy rights, Accordingly, we can recommend sufficient awareness that makes people aware of the magnitude of the tragedy that this crime leaves behind and its danger to society and the sin and punishment that will befall its owner on the Day of Resurrection. "
مذكرة ماستر
Keywords: مجهولي النسب- عقد الزاج- القانون الوضعي; Of unknown parentage - marriage contract - positive law